2012
DOI: 10.1007/s10495-012-0750-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced apoptosis in retinal pigment epithelium under inflammatory stimuli and oxidative stress

Abstract: Age-related macular degeneration (AMD) is a neurodegenerative disease that causes irreversible central vision loss in the elderly. Retinal pigment epithelium (RPE) has been found to be a key component in AMD pathogenesis. The Ccl2−/−/Cx3cr1−/− (DKO) mouse on Crb1rd8 background is created as an AMD model, developing AMD-like retinal lesions. Our study aimed to examine RPE apoptosis in DKO mouse and human ARPE-19 cell line. DKO RPE expressed higher apoptotic proteins when compared with age-matched wild type (WT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…We have reported an elevated FasL-mediated RPE apoptosis under inflammation and oxidative stress in the cultured RPE cells of DKO rd8 mouse than that of WT (Wang et al, 2012). Higher levels of Bax transcript and lower ratios of Bcl2/Bax were also detected in DKO rd8 mouse eyes compared with WT (Cao et al, 2010).…”
Section: Discussionmentioning
confidence: 89%
“…We have reported an elevated FasL-mediated RPE apoptosis under inflammation and oxidative stress in the cultured RPE cells of DKO rd8 mouse than that of WT (Wang et al, 2012). Higher levels of Bax transcript and lower ratios of Bcl2/Bax were also detected in DKO rd8 mouse eyes compared with WT (Cao et al, 2010).…”
Section: Discussionmentioning
confidence: 89%
“…A number of studies found that apoptosis plays an important role in retinal cell death, both in physiological and pathological conditions, and particularly in AMD [5,31,32,33]. Dunaief et al [34], for example, demonstrated in vivo the involvement of apoptosis in RPE cell death at the margins of GA in dry AMD eyes, and Hinton et al [31] showed an involvement of apoptosis in choroidal neovascularization membranes of patients suffering from neovascular AMD.…”
Section: Discussionmentioning
confidence: 99%
“…Dunaief et al [34], for example, demonstrated in vivo the involvement of apoptosis in RPE cell death at the margins of GA in dry AMD eyes, and Hinton et al [31] showed an involvement of apoptosis in choroidal neovascularization membranes of patients suffering from neovascular AMD. Numerous in vitro investigations revealed that retinal cell apoptosis is mediated by oxidative stress [5,35,36]. In addition, apoptosis due to oxidative stress is characterized not only by elevated caspase levels, but also by an increase in the proapoptotic protein BAX and a decrease in the antiapoptotic protein Bcl-2 [27,37,38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysfunction of autophagic mechanisms may lead to increases in protein-misfolding and oxidative stress, contributing to the overall para-inflammatory state and driving the system towards a pathological equilibrium. We have also shown enhanced apoptosis in cultured RPE cells under inflammatory stimuli and oxidative stress (Wang et al, 2012). …”
Section: The Aging Paradigm In Amdmentioning
confidence: 93%